2023
DOI: 10.3390/ijms24032415
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-Type Shifting in Sarcopenia of Old Age: Proteomic Profiling of the Contractile Apparatus of Skeletal Muscles

Abstract: The progressive loss of skeletal muscle mass and concomitant reduction in contractile strength plays a central role in frailty syndrome. Age-related neuronal impairments are closely associated with sarcopenia in the elderly, which is characterized by severe muscular atrophy that can considerably lessen the overall quality of life at old age. Mass-spectrometry-based proteomic surveys of senescent human skeletal muscles, as well as animal models of sarcopenia, have decisively improved our understanding of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 586 publications
0
28
0
Order By: Relevance
“…Excellent markers of the various subtypes of myofibers are represented by slow myosin heavy chain MyHC-1(beta) and the fast myosin heavy chains MyHC-2a, MyHC-2x and MyHC-2b [274]. The biochemical profiling of the contractile apparatus of skeletal muscles has recently been reviewed and this article lists the most abundant fiber type-specific markers, i.e., isoforms of myosin heavy chains, myosin light chains, troponins and tropomyosins, that were confirmed by proteomics [47]. The identification of individual fiber types using contractile apparatus proteins can be conveniently combined with reliable markers that belong to the Ca 2+ -handling complexes of skeletal muscles.…”
Section: Basic and Applied Myologymentioning
confidence: 98%
See 2 more Smart Citations
“…Excellent markers of the various subtypes of myofibers are represented by slow myosin heavy chain MyHC-1(beta) and the fast myosin heavy chains MyHC-2a, MyHC-2x and MyHC-2b [274]. The biochemical profiling of the contractile apparatus of skeletal muscles has recently been reviewed and this article lists the most abundant fiber type-specific markers, i.e., isoforms of myosin heavy chains, myosin light chains, troponins and tropomyosins, that were confirmed by proteomics [47]. The identification of individual fiber types using contractile apparatus proteins can be conveniently combined with reliable markers that belong to the Ca 2+ -handling complexes of skeletal muscles.…”
Section: Basic and Applied Myologymentioning
confidence: 98%
“…Thus, a detailed understanding of normal muscle function and its cellular regulation including the dynamics of the skeletal muscle proteome, as compared to muscle wasting, is important for diverse biological and biomedical disciplines. This includes crucial aspects of lifestyle biology, health science and clinical medicine, including sports and exercise physiology [39,40], electro-stimulation therapy, research into skeletal muscle plasticity [43,257], disuse-related muscular atrophy and the effects of re-innervation [41,258,259], space flight medicine [260,261], neuromuscular diseases [44,45], frailty-associated muscle aging and biogerontology [47,[262][263][264], forensic medicine [265,266] and the meat industry [267,268]. Important topics in muscle cell biology that are gaining steady interest are the regulation of skeletal muscle mass [269], myokine signaling [270] and muscle-bone-fat crosstalk [271].…”
Section: Basic and Applied Myologymentioning
confidence: 99%
See 1 more Smart Citation
“…While other -omics-based approaches exist (i.e., genomics, epigenomics, transcriptomics, and metabolomics), it has been posited that proteomic signatures likely best translate to cellular and tissue phenotypes (17). Past proteomic investigations have provided tremendous insight as to how myofiber type, aging, and exercise training affect the skeletal muscle molecular milieu (1,14,(18)(19)(20)(21)(22). Notwithstanding, skeletal muscle-based proteomics poses technical challenges.…”
Section: Introductionmentioning
confidence: 99%
“…This work paves the way for deeper investigation on the TGF-β/BMP balance, which may lead to the development of new strategies to fight against muscle atrophy. Dowling et al [6] addressed the potential use of markers for addressing the progressive loss of muscle mass and strength in elderlies, i.e., sarcopenia. The authors compiled proteomic data from elderlies and aged rodents and observed that the fiber shift (from fast to slow) appearing during aging may be a good readout for witnessing the appearance of sarcopenia.…”
mentioning
confidence: 99%